PENGARUH TERPAAN INFORMASI AKUN INSTAGRAM @mahasiswa_universitasriau TERHADAP PENGETAHUAN KEGIATAN AKADEMIK MAHASISWA UNIVERSITAS RIAU - Wulandari, Ayu; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Instagram is one of the social media that not only allows users to interact with other users, but can also be used as a disseminator of various information. Because Instagram provides many features to facilitate users in communication and Instagram as a medium can provides infomation that can be used by personal, community, organization and others. Exposure to messages on social media Instagram becomes a medium for disseminating information that has the potential for users to obtain information. One of the uses of social media Instagram as an information media in the campus environment of Riau University is also used by one particular account that spread academic information to its followers, named @mahasiswa_universitasriau. The theory used in this study was the S – R ( Stimulus – Response) theory. The purpose of this study was to determine the influence of Instagram account @mahasiswa_universitasriau on  academic activies knowledge of Riau University students.This research used quantitative research method, with explanative research type. The data collection technique was through the spread of questionnaires using google form online to Riau University student who followed the @mahasiswa_universitasriau Instagram account with 39.600 of populations and the number of samples were 166 respondents, using the unknown population which was determined by simple random sampling tecnique. The data analysis technique in this study used simple linear regression analysis and determination test used SPSS 16.0 software for windows.The result of this research showed the large of influence of exposure to information Instagram account @mahasiswa_universitasriau on academic activities knowledge of Riau University Students is in the weak category . It can be seen from the result of simple linear  regression in this research was equal to Y = 26,686 + 0,536X + e. The constant value was 26,686 and the variable coefficient of exposure to Instagram account information value equal to 0,536 . Meanwhile t count 8,226 was bigger when compared to t table equal to 1,974, with significance level 0,000 was smaller than α= 0,05. It means Ha was acceppted H0 was rejected. Based on the table“Model Summary” shows that the value of R = 0,540a and the coefficient of determination (Rsquare) was 0,292. This figure shows the understanding that the influence of exposure to information on Instagram account  @mahasiswa_universitasriau on the academic activities knowledge of Riau University Students by 29,2% with the category of weak or low. While the remaining 70,8% was influenced by other variables which are not included in this research.